THE FALL OF SOFIA AND PLOTINUS' METAPHYSICS FROM GNOSTIC DENIAL TO AFFIRMATION OF THE COSMOS - Calabrese, Claudio César; Junco, Ethel (PROUniversitaria Publishing House, 2026)
This article examines the controversy between Plotinus and the Gnostics regarding the origin and value of the sensible world, focusing on Enn. II, 9, 33. It shows that, although both systems share a mystical horizon and a language of ascension toward the divine, they differ radically in their understanding of the cosmos and the condition of the soul. Valentinian gnosis interprets the world as the result of a fall in the Pleroma, generated by Sophia's audacity in attempting to have a direct apprehension of the Father. As a result of this rupture, both the ignorant Demiurge and the material prison in which the soul has become trapped arose. Salvation, therefore, consists in remembering its origin and escaping from matter. This implies a negative view of the cosmos. Plotinus rejects this perspective as theologically impossible and as an obstacle to understanding the world, since the higher hypostases cannot err; the world does not come from a fault but from the overabundance of the One. Emanation is order and continuity, not violence and rupture. Matter is not the cause of evil because it is evil, but because it is deprivation. The cosmos, therefore, is a beautiful and necessary image of the Intellect, and the soul always retains an essential relationship with its origin. The controversy with the Gnostics was decisive in Plotinus's refinement of his metaphysics and his defense of the positivity of the world as an expression of divine intelligence. © 2026, PROUniversitaria Publishing House. All rights reserved.